CFD Analysis and Electrical Efficiency Improvement of a Hybrid PV/T Panel Cooled by Forced Air Circulation - Gökhan Ömeroğlu (International Journal of Photoenergy)
The thermal and electrical efficiency of a custom-designed PV/T panel cooled by forced air circulation was investigated by experimental and computational fluid dynamics (CFD) analysis. Experiments were carried out with four different array configurations, under constant irradiation of 1100 W/m2 and 3 different air velocities (3.3 m/s, 3.9 m/s, and 4.5 m/s). The heat transfer surface area and forced air circulation are known to positively affect the total heat transfer, and therefore, it is foreseeable that an increased number of fins and higher air velocities will help maintain the electrical efficiency of the panel at higher levels. The main objective of this study is to determine the critical threshold for the abovementioned parameters as well as to show how important parameters, such as fin arrangement and consequent turbulent air flows, are for satisfying the heat removal needs. Highest efficiency was achieved with a 108 pc type 1 arrangement at 12.02% as expected. Nevertheless, while the 108 pc type 2 arrangement could maintain the electrical efficiency at 11.81%, a close level of 11.55% could be obtained with a 54 pc type 2 arrangement. Experimental results are compared with ANSYS Fluent program, and the effect of the number and arrangement of the fins on the efficiency of the panel has been shown.